Dual Band RCS Reduction Using Modulated Grooves in A Conducting Plane - Lee, Sangsu; Jun, Heejae; Jung, Kyung Young; Choo, Hosung; Hong, Ic Pyo; Park, Yong Bae (Journal of Electrical Engineering and Technology, 2019)
An electromagnetic boundary-value problem of modulated grooves in a conducting plane is rigorously solved based on the Fourier transform, eigenfunction expansion, and mode matching method. Radar cross section (RCS) of the modulated grooves is represented in a series form and calculated while varying depth, width, and period of the grooves to investigate scattering characteristics of dual band RCS reduction.
Keywords: Conducting planes; Dual Band; Eigenfunction expansions; Electromagnetic boundary value problems; Mode matching method; Modulated grooves; Rcs reductions; Scattering char-acteristics; Mode matching method; Modulated grooves; Radar cross section